2011
DOI: 10.1016/j.envres.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations between brominated flame retardants in human milk and thyroid-stimulating hormone (TSH) in neonates

Abstract: Background Brominated flame retardants (BFRs) have been in widespread use in a vast array of consumer products since the 1970s. The metabolites of some BFRs show a structural similarity to thyroid hormones and experimental animal studies have confirmed that they may interfere with thyroid hormone homeostasis. A major concern has been whether intrauterine exposure to BFRs may disturb thyroid homeostasis since the fetal brain is particularly susceptible to alterations in thyroid hormones. However, few reports on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 47 publications
1
36
1
Order By: Relevance
“…One caveat, however, could be the limited number of samples, which hampered evaluation of weak or moderate associations. Eggesbø et al (2011) studied the association between levels of HBCDDs in human milk and neonatal thyroid-stimulating hormone (TSH). No association was found adjusting for a number of confounders, including environmental toxicants.…”
Section: Consideration Of Critical Effects and Possibilities For Derimentioning
confidence: 99%
See 1 more Smart Citation
“…One caveat, however, could be the limited number of samples, which hampered evaluation of weak or moderate associations. Eggesbø et al (2011) studied the association between levels of HBCDDs in human milk and neonatal thyroid-stimulating hormone (TSH). No association was found adjusting for a number of confounders, including environmental toxicants.…”
Section: Consideration Of Critical Effects and Possibilities For Derimentioning
confidence: 99%
“…To evaluate the association between HBCDDs and neonatal TSH, Eggesbø et al (2011) studied HBCDDs measured in milk samples from 193 women who were part of the 'Norwegian Human Milk Study' (HUMIS), [2003][2004][2005][2006]. TSH was measured in babies three days after delivery as part of the routine national screening program for early detection of congenital hypothyroidism.…”
Section: Observations In Humansmentioning
confidence: 99%
“…Many epidemiological studies that evaluate associations of PBDEs exposure and thyroid hormones in adults and newborns have been published previously, but their results are not consistent (Hagmar et al, 2001;Mazdai et al, 2003;Herbstman et al, 2008;Turyk et al, 2008;Dallaire et al, 2009;Kim et al, 2009;Roze et al, 2009;Chevrier et al, 2010;Zhang et al, 2010;Chevrier et al, 2011;Eggesbø et al, 2011;Gascon et al, 2011;Lin et al, 2011). A few studies report the negative impact of cord blood PBDEs on levels of human thyroid hormones after in utero exposure (Herbstman et al, 2008;Lin et al, 2011), but most studies conducted in humans have found no correlations.…”
Section: Pbdes and Thyroid Hormonesmentioning
confidence: 95%
“…Breast milk HBCD levels are positively correlated with the number of stereo and video electronics in a home, and are lower in women who regularly choose organic foods compared to those who do not, according to as series of tests performed on Boston mothers (Carignan et al, 2012). Eggesbø et al (2011) argues that breast milk HBCDs are not related to cord blood TSH. Asante et al (2011) calculates that the ΣHBCDs daily intake for a breastfed infant through breastfeeding is 0.003 µg/kg b.w./day in Ghana.…”
Section: Hbcds and Human Healthmentioning
confidence: 99%
See 1 more Smart Citation